Seasonal influenza vaccination in Kenya: an economic evaluation using dynamic transmission modelling. - Dawa, J; Emukule, GO; Barasa, E; Widdowson, MA; Anzala, O; van Leeuwen, E; Baguelin, M; Chaves, SS; Eggo, RM (BioMed Central, 2020)
Background: There is substantial burden of seasonal influenza in Kenya, which led the government to consider introducing a national influenza vaccination programme. Given the cost implications of a nationwide programme, local economic evaluation data are needed to inform policy on the design and benefits of influenza vaccination. We set out to estimate the cost-effectiveness of seasonal influenza vaccination in Kenya. Methods: We fitted an age-stratified dynamic transmission model to active surveillance data from patients with influenza from 2010 to 2018. Using a societal perspective, we developed a decision tree cost-effectiveness model and estimated the incremental cost-effectiveness ratio (ICER) per disability-adjusted life year (DALY) averted for three vaccine target groups: children 6–23 months (strategy I), 2–5 years (strategy II) and 6–14 years (strategy III) with either the Southern Hemisphere influenza vaccine (Strategy A) or Northern Hemisphere vaccine (Strategy B) or both (Strategy C: twice yearly vaccination campaigns, or Strategy D: year-round vaccination campaigns). We assessed cost-effectiveness by calculating incremental net monetary benefits (INMB) using a willingness-to-pay (WTP) threshold of 1–51% of the annual gross domestic product per capita (USD17–USD872). Results: The mean number of infections across all ages was 2–15 million per year. When vaccination was well timed to influenza activity, the annual mean ICER per DALY averted for vaccinating children 6–23 months ranged between USD749 and USD1385 for strategy IA, USD442 and USD1877 for strategy IB, USD678 and USD4106 for strategy IC and USD1147 and USD7933 for strategy ID. For children 2–5 years, it ranged between USD945 and USD1573 for strategy IIA, USD563 and USD1869 for strategy IIB, USD662 and USD4085 for strategy IIC, and USD1169 and USD7897 for strategy IID. For children 6–14 years, it ranged between USD923 and USD3116 for strategy IIIA, USD1005 and USD2223 for strategy IIIB, USD883 and USD4727 for strategy IIIC and USD1467 and USD6813 for strategy IIID. Overall, no vaccination strategy was cost-effective at the minimum (USD17) and median (USD445) WTP thresholds. Vaccinating children 6–23 months once a year had the highest mean INMB value at USD872 (WTP threshold upper limit); however, this strategy had very low probability of the highest net benefit. Conclusion: Vaccinating children 6–23 months once a year was the most favourable vaccination option; however, the strategy is unlikely to be cost-effective given the current WTP thresholds.